Don't Shrink me to the Size of a Bullet: The Works of Hiwa K. - Downey, Anthony (Koenig Books : London, 2017)
Gruijthuijsen, Krist; Mertens, Heike; Abu Hamdan, Lawrence; Szylak, Aneta; Soh Bejeng Ndikung, Bonaventure; Ginwala Natasha
tentoonstellingscatalogus, KW Institute for Contempoary Art, Berlin 2017
boek
Keywords: Hiwa K